Radion Effects on Bhabha Scattering - Bang, Ha Huy; Duong, Pham Que; Thu Huyen, Nguyen Thi; Thuy Linh, Nguyen Thi; Nhu Xuan, Nguyen (VNU Journal of Science: Mathematics - Physics, 2020)
In this article, we have considered the possible signatures of radion through Bhabha scattering. The numerical results show that the total cross section with radion effects are about 1.43-19.70 pb. This could have important implications for radion searches and for the measurement of the cross-section of the Bhabha scattering.